CONTRIBUTION TO KNOWLEDGE OF THE FAUNA OF BARK BEETLES (COLEOPTERA, CURCULIONIDAE, SCOLYTINAE) ON DECIDUOUS WOODY PLANTS IN SERBIA (Acta Entomologica Serbica, 2015)
Not much information has been published about the distribution and hosts of  bark beetles on deciduous woody plants in Serbia. The present paper gives the localities and hosts in Serbia of 23 species of these insects from seven tribes and 10 genera (Scolytus, 10 species; Ernoporicus, two; Hylesinus, two; Taphrorychus, two; Xyleborus, two; Ernoporus, one; Pteleobius, one; Trypodendron, one; Xyleborinus, one; and Xylocleptes, one).